Streaming Performance Analysis of Virtual Objects in Augmented Reality Cloud Based on X86 and ARM Processor Types - arda surya editya (International Journal of Science, Engineering, and Information Technology, 2019)
Augmented Reality is a technology that makes it possible to create 3D objects in the real world with the help of a camera on a gadget. In its development, Augmented Reality technology began to be developed and combined with cloud computing technology. With the existence of Cloud computing technology Augmented reality can work more efficiently because all 3D objects can be stored on the Cloud. With the development of this technology, the author feels the need to conduct an analysis to determine the right processor in making the Augmented Reality Cloud application, because there is no research that is used as a reference in developing hardware and software used for Augmented Reality Cloud. Result of this experiment can be concluded CISC architecture processors have faster time in detecting markers compared to RISC architecture processors, because CISC processor speeds are faster than RISC processors.